Serum Albumin in Nasal Drug Delivery Systems: Exploring the Role and Application - Sandra Aulia Mardikasari; Gábor Katona; Ildikó Csóka (MDPI AG, 2024)
The application of serum albumin in various types of formulations has emerged as a valuable option in biomedical research, especially in the field of nasal drug delivery systems. A serum albumin-based carrier system has been employed due to several benefits, such as enhancing drug solubility and stability, generating the desired controlled release profile, and developing favorable properties with respect to the challenges in nasal conditions, which, in this case, involves hindering rapid elimination due to nasal mucociliary clearance. Accordingly, considering the important role of serum albumin, in-depth knowledge related to its utilization in preparing nasal drug formulation is highly encouraged. This review aimed to explore the potential application of serum albumin in fabricating nasal drug formulations and its crucial role and functionality regarding the binding interaction with nasal mucin, which significantly determines the successful administration of nasal drug formulations.